1990
DOI: 10.1007/bf00007121
|View full text |Cite
|
Sign up to set email alerts
|

Emergence, maturation and upstream oviposition flights of Plecoptera from the Breitenbach, with notes on the adult phase as a possible control of stream insect populations

Abstract: Upstream oviposition flights of several Plecoptera species of the genera Leuctra, Nemoura, Isoperla and Siphonoperla along the Breitenbach, Hesse, Germany are inferred from 1. oviposition occuring upstream from emergence areas; 2. size differences and size-shifts between emerging and egg-laying females; 3. concentration of oviposition in upstream sections of the emergence area. The last point relies on direct catches of egg-laying females with sticky traps, and on over-representation of old, mature females in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 27 publications
(43 reference statements)
7
55
0
Order By: Relevance
“…Our results (particularly the high percentage of pollen grains in the diet) agree with the general pattern shown for other Chloroperlidae adults (Zwick 1990;Tierno de Figueroa & Sánchez-Ortega 1999;Derka et al 2004), but the presence of animal suggests an interesting and new finding. Up to now, data about animal feeding in adult stoneflies were limited to scarce observations and almost every time in Nemouroidea (Frison 1929;Salveit 1977;Rotheray & Liston 1985;.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results (particularly the high percentage of pollen grains in the diet) agree with the general pattern shown for other Chloroperlidae adults (Zwick 1990;Tierno de Figueroa & Sánchez-Ortega 1999;Derka et al 2004), but the presence of animal suggests an interesting and new finding. Up to now, data about animal feeding in adult stoneflies were limited to scarce observations and almost every time in Nemouroidea (Frison 1929;Salveit 1977;Rotheray & Liston 1985;.…”
Section: Resultssupporting
confidence: 90%
“…Rotheray & Liston (1985) observed a Chloroperla tripunctata (Scopoli, 1763) that seemed to feed on a sawfly (Tenthredinidae). More recently, Rupprecht (1990) demonstrated that Siphonoperla torrentium (Pictet, 1842) can metabolize food ingested during the adult stage and Zwick (1990) pointed out that this species gains weight during its adult life by ingesting food (consisting in Pinaceae pollens). Tierno de Figueroa & Sánchez-Ortega (1999) showed that Chloroperla nevada Zwick, 1967 adults change the proportion of dietary components over the flight period in relation to their availability.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in sex ratio have been observed for several species of stoneflies (Zwick 1990, Sheldon 1999, Petersen et al, 2006. Our study suggests that sex ratios of K. kuscheli and A. michaelseni were male-biased in Baggilt stream.…”
Section: La Hoyamentioning
confidence: 61%
“…Many of the taxa that are numerically abundant in upland streams, notably Plecoptera, Trichoptera and Diptera, have adult stages which are effectively terrestrial, and which spend their lives in the riparian zone (Collier and Smith, 1998;Petersen et al, 1999;Delettre and Morvan, 2000;Briers et al, 2002). Mortality of adult stages in the terrestrial environment is high, in the region of 90% (Jackson and Fisher, 1986;Werneke and Zwick, 1992;Enders and Wagner, 1996), and hence factors influencing the distribution, survival and reproductive success of adults may be important in determining the abundance and distribution of larval stages (Statzner, 1977;Zwick, 1990;Timm, 1994;Harrison and Hildrew, 1998).…”
Section: Introductionmentioning
confidence: 99%